The Origin of the Different Waves of Iranian Migration in France - Vahabi, Nader (Cultural and religious studies, 2016)
From the knowledge exile of the 19th century, the profile changed towards the political refugee in 1908. French was then recognized as the official language in administration. Iranian migration later took on another dimension after the 1953 Coup, a politicization that reached a peak with the arrival in Paris of Khomeini on August 2, 1978. In spite of this migratory tradition, about 4,000 persons before the revolution, the majority being from the political and financial elite, these migratory flows amplified in the middle of the 1980s, in such a way that at the end of December 2014, there were 31,000 Iranians in France. This new phase which included four waves, from a sociological point of view, can be called the diasporaisation of Iranian migration. The socio-economic profile goes from the urban elite: lawyers, officials, journalists, teachers, doctors, nurses, magistrates, military officials, company directors, political exiles, etc., to artisans such as shopkeepers, garage owners, building contractors… and finally from the skilled labourer, on through to unskilled workers in building, restauration or removals.